2021
DOI: 10.25259/sni_97_2021
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative hematoma volume can predict chronic subdural hematoma recurrence

Abstract: Background: We routinely measured the exact chronic subdural hematoma (CSDH) volume during single burr hole surgery. To date, several risk factors have been reported for CSDH recurrence, including sex, hematoma volume and degree of midline shift calculated from computed tomography, use of anticoagulants or antiplatelet medications, and alcohol consumption habits. The aim of this study was to clarify whether hematoma volume, in conjunction with other factors, can predict recurrence. Methods: We retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Some studies believe that middle meningeal artery embolization can prevent hematoma expansion and recurrence in patients with recurrence after multiple surgical treatments [ 28 ]. At present, bilateral drilling drainage is recommended for most patients with bilateral CSDH [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies believe that middle meningeal artery embolization can prevent hematoma expansion and recurrence in patients with recurrence after multiple surgical treatments [ 28 ]. At present, bilateral drilling drainage is recommended for most patients with bilateral CSDH [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified demographic, comorbid, preoperative, and postoperative factors associated with CSDH recurrence. [ 1 , 3 , 5 , 8 , 10 - 13 , 16 - 18 , 21 , 24 , 25 , 29 , 32 - 34 , 37 , 41 , 42 , 44 ] Examples include advanced age, bleeding tendency, brain atrophy, alcohol abuse, bilateral hematoma, hematoma density, size or volume of the hematoma, midline shift, diabetes mellitus, postoperative posture, postoperative subdural air accumulation, inflammatory cytokines, and some technical aspects of surgery. Identifying these factors allow clinicians to better manage patients deemed to be at high risk for recurrence.…”
Section: Introductionmentioning
confidence: 99%